(untitled) ("Conference on Universal Science Research 2023", 2023)
This article presents a typology of femininity in advertising discourse, examining the impact of advertising on women’s self-esteem and body image, the reinforcement of gender stereotypes, and ethical considerations. The linguistic features used in ads targeting women are analyzed, with examples of phrases creating unrealistic expectations for women. Studies on exposure to advertisements portraying unrealistic beauty standards are discussed, highlighting the negative impact on body image and self-esteem. The reinforcement of traditional roles and language emphasizing femininity and domesticity perpetuate harmful gender stereotypes. Advertisers have a responsibility to promote positive societal norms and values, including promoting positive body image and gender equality. Responsible advertising practices can contribute to a more equitable and just society.